Changes in human calcaneal morphology throughout the Pleistocene-Holocene Levant - Dann, Ariana; Pokhojaev, Ariel; Anton, Marie; Yalovitsky, Guy; Kallevag-Pelleg, Ruth; May, Hila (Frontiers in Earth Science, 2024)
The calcaneal morphology changed considerably during human evolution to enable efficient bipedal locomotion. However, little information exists regarding its adaptation to changes in habitual activities following the transition to a sedentary lifestyle. We aimed to examine changes in calcaneal morphology during the Pleistocene-Holocene Levant in light of sexual dimorphism. We studied three archaic Homo sapiens calcanei dated to the Middle and Upper Paleolithic, 23 Natufian hunter-gatherers, 12 Pre-Pottery Neolithic early farmers, and 31 Chalcolithic farmers. The calcanei were scanned via a surface scanner and measured, and bone proportions were calculated. Measurements included the height, length, and width of various calcaneal elements. The sex of each individual was determined using methods based on calcaneal morphology. The validity of these methods was tested in those individuals who had the pelvis (92.3% agreement rate). Accordingly, the sample included 59.4% males and 40.6% females. Most calcaneal indices were sexindependent, except for the relative width, relative anterior length, and the cuboid index.Temporal trends between the Natufian and Chalcolithic periods were more pronounced among males than females. While in the proximal calcaneus, the temporal trend was similar between males and females, it differed in the distal part and articular facets. The calcanei of archaic H. sapiens exceeded the average of the Natufian hunter-gatherer for most variables, though the trend varied. To conclude, males and females were affected differently by the changing environment. The calcanei of archaic H. sapiens were better adapted for activity involving high mobility, independent of sex. During the transition to a sedentary way of life, different factors probably designed the male and female calcaneus. These could include factors related to the sexual division of labor, adaptation to lengthy standing, and changes in footwear.